Hospitalité publique et altérité tsigane : du modèle d’intégration au paradigme assimilationniste - Caroline Trouillet (Conserveries Mémorielles)
This article deals with the relation between our french Nation-State and identities of communities settled inside its borders through time. More precisely, we read this constantly changing relation using the concept of state hospitality towards the population of roma migrants from Bulgaria and Romania who live around Paris. Indeed, the roma migrant is a « stranger from inside » (Missaoui 1999) who has always drawn hatred and troubles while playing a civilizing role. As a result, he appears more than any other stranger as the most significant witness of our current society’s relationship with theother, whether it be migrant or immigrant. After focusing on the sociologic detachment the researcher must have when it comes to otherness, we show how the french integration model can be revealed through the way roma strangers have been hosted and controlled since entering the insertion project we studied : the « insertion village ». The deeply contradictory dimension of this model reveals how the paradigm of insertion is irrelevant when it comes to the migration and settlement of roma people on the local and national space. Since the « insertion village » as it is conceived implies a colonial relationship between strangers and indigenous people, this article shows how the project draws its rules from essentialist thoughts that inspired 19th century paternalist structures aimed at controlling workers' practices.